2016
DOI: 10.1002/eqe.2719
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional beam‐truss model for reinforced concrete walls and slabs – part 1: modeling approach, validation, and parametric study for individual reinforced concrete walls

Abstract: SUMMARYA three-dimensional beam-truss model for reinforced concrete (RC) walls developed by the first two authors in a previous study is modified to better represent the flexure-shear interaction and more accurately capture diagonal shear failures under static cyclic or dynamic loading. The modifications pertain to the element formulations and the determination of the inclination angle of the diagonal elements. The modified beam-truss model is validated using the experimental test data of eight RC walls subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 13 publications
1
37
0
1
Order By: Relevance
“…The experimental results indicated that the shear capacities of shear wall systems with replaceable fuses were close to that of the conventional shear wall system. Moreover, the inelastic deformation and damage of specimens were concentrated in the fuse section as expected [44,45]. In order to reduce the damage at the bottom of the shear wall, new replaceable foot parts for the shear wall were proposed [46]; it was experimentally revealed that the proposed foot parts wall could greatly minimize the damage at the bottom of the shear wall.…”
Section: Coupling Beam Of Shear Wallmentioning
confidence: 67%
“…The experimental results indicated that the shear capacities of shear wall systems with replaceable fuses were close to that of the conventional shear wall system. Moreover, the inelastic deformation and damage of specimens were concentrated in the fuse section as expected [44,45]. In order to reduce the damage at the bottom of the shear wall, new replaceable foot parts for the shear wall were proposed [46]; it was experimentally revealed that the proposed foot parts wall could greatly minimize the damage at the bottom of the shear wall.…”
Section: Coupling Beam Of Shear Wallmentioning
confidence: 67%
“…The effect of aggregate interlock is not modeled. Confined edge beams in the slab, such as that shown in Figure (a), are modeled with beam elements that have flexural rigidity in and out of plane, similar to the boundary elements of RC walls as discussed in the companion paper . For the slab BTM, the torsional rigidity of each beam is modeled as bilinear perfectly plastic, with the gross elastic torsional rigidity up to the torsional cracking strength, which is calculated based on the space truss model for torsion .…”
Section: Three‐dimensional Beam–truss Model For Slabsmentioning
confidence: 99%
“…The strut running from the bottommost coupling beam to the base corner is used to determine the diagonal angle. The nominal moment capacity of the wall is the moment for which the peak tension strain of longitudinal steel reaches 1% or the peak compressive strain of concrete reaches 0.3%. If V b , cp is smaller than that required for case , the coupled walls are treated as individual walls uniform over their height when determining the diagonal angle (i.e., using the diagonal angle determination for walls uniform over their height; see the companion paper ). The effect of the coupling forces M A , M B , and V cpl is taken into account when calculating M n for the first estimate of diagonal angle.…”
Section: Determination Of Inclination Angle For Diagonal Elements In mentioning
confidence: 99%
See 2 more Smart Citations